2010
DOI: 10.2975/33.3.2010.190.199
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the thinking skills for work program in a psychosocial clubhouse.

Abstract: The findings support the feasibility and promise of implementing the Thinking Skills for Work program in the context of supported employment provided at psychosocial clubhouses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 38 publications
1
28
0
Order By: Relevance
“…This percentage was not better than those reported by SoFA for HOPE alone either (HOPE = ~22%). Conversely, previous research has reported improved employment outcomes for CR and vocational training (TSW + Clubhouse = ~36 %) (McGurk et al, ).…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This percentage was not better than those reported by SoFA for HOPE alone either (HOPE = ~22%). Conversely, previous research has reported improved employment outcomes for CR and vocational training (TSW + Clubhouse = ~36 %) (McGurk et al, ).…”
Section: Discussionmentioning
confidence: 81%
“…Duration and intensity of the cognitive training were based upon previous findings of CR embedded within a comprehensive rehabilitation setting (e.g., CR+vocational support) (McGurk et al, , ). A noteworthy difference between the current study and previous work is that TSW includes collaboration with employment specialists during CR delivery, whereas all participants in this study were near to complete or had already completed the HOPE program.…”
Section: Discussionmentioning
confidence: 99%
“…Subjective well-being (naBeR, et al, 2005;lamBeRt, et al, 2006), quality of life (yunG, et al, 1996), cognition (GReen, et al, 2008;haRvey, et al, 2006;KeeFe, et al, 2010) and psychosocial performance, including employment (lehman, et al, 2002;evans, et al, 2004;mCGuRK, et al, 2010), have become endpoints of interest and goals for patients, families, clinicians and researchers (Kane et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Adults with serious mental illness face significant challenges as they learn skills for a productive and satisfying life (McGurk et al, 2010; Tsang et al, 2010), with profound cognitive and social deficits interfering with the ability to navigate the job market and community resources (Bowie et al, 2012; Twamley et al, 2012; Reddy et al, 2014). These individuals may be referred to day treatment programs that tend to rely on traditional modes of treatment planning, where treatment providers decide on a ‘course’ of treatment and create a treatment plan that may be updated at only 6-month intervals, if then, and may not contain an evaluation of treatment effectiveness.…”
Section: Introductionmentioning
confidence: 99%